Effect of PAK1 gene silencing on proliferation and apoptosis in hepatocellular carcinoma cell lines MHCC97-H and HepG2 and cells in xenograft tumor. Issue 4 (July 2018) - Zhang, Zhi-Lei; Liu, Guang-chao; Peng, Li; Zhang, Chong; Jia, Yu-Ming; Yang, Wu-Han; Mao, Lei
Abstract This study intends to explore the effect of the PAK1 gene silencing on apoptosis and proliferation of hepatocellular carcinoma (HCC) MHCC97-H and HepG2 cells and cells in xenograft tumor. MHCC97-H and HepG2 cells and mice with xenograft tumor in vivo were randomly divided into control, empty vector and PAK1 shRNA groups. Morphology and the expression of green fluorescent protein of MHCC97-H and HepG2 cells and cells in xenograft tumor were observed. MTT assay and flow cytometry were used to detect proliferation, cell cycle and apoptosis of MHCC97-H and HepG2 cells and cells in xenograft tumor. The expressions of PAK1, PCNA, Ki67, Cyclin E, CDK2, p21, p53, Bax and Bcl-2 were measured using the quantitative reverse transcription polymerase chain reaction and western blotting. Compared with the control and empty vector groups, number of adherent cells of MHCC97-H and HepG2 cells and cells in xenograft tumor was reduced, and green fluorescent cells became round and reduced in the PAK1 shRNA group. Cell proliferation, the cells at S phase, the mRNA and protein expressions of PAK1, PCNA, Ki67, Cyclin E, CDK2 and Bcl-2 of MHCC97-H and HepG2 cells and cells in xenograft tumor were decreased, while the cells at G1 phase, apoptosis rate, the mRNA and protein expressions of p21, p53 and Bax of MHCC97-H and HepG2 cells and cells in xenograft tumor were increased in the PAK1 shRNA group. PAK1 gene silencing decreases proliferation of MHCC97-H cells, HepG2 cells and cells in xenograft tumor through the p53/p21 pathway.